2021
DOI: 10.1037/adb0000771
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity in daily marijuana and alcohol among emerging adults.

Abstract: Objective: The relationship between marijuana and alcohol use among late adolescents was examined as whether marijuana use was related to quantity of alcohol consumed that day, and whether changes in marijuana and alcohol use frequency over 3 years were related. Method: College students (n = 375) reported marijuana and alcohol use for 28 days over 3 years. Results: Within-day analyses showed that more alcohol was consumed on days on which marijuana was used. Co-use varied by alcohol use problems, day of week, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“… 45 For same-day co-use, several papers found that more alcohol was consumed on days marijuana was also used relative to days that only alcohol was used. 46 48 Between-person findings in these papers provided some evidence that greater average alcohol intake was associated with more frequent SAM use 32 and less frequent same-day co-use. 46 , 47 …”
Section: Resultsmentioning
confidence: 91%
“… 45 For same-day co-use, several papers found that more alcohol was consumed on days marijuana was also used relative to days that only alcohol was used. 46 48 Between-person findings in these papers provided some evidence that greater average alcohol intake was associated with more frequent SAM use 32 and less frequent same-day co-use. 46 , 47 …”
Section: Resultsmentioning
confidence: 91%
“…Simultaneous alcohol and cannabis use (also sometimes called simultaneous alcohol and marijuana use) is common in the U.S. (Subbaraman & Kerr, 2015, 2020), particularly among college students (White et al, 2019). Simultaneous use has been linked to increased alcohol and cannabis consumption and negative consequences compared to single-substance use (Ito et al, 2021; Lee et al, 2020; Linden-Carmichael et al, 2020; Metrik et al, 2018). However, almost no research has explored whether college students plan for simultaneous use or if it is unplanned and incidental, for example, unintentionally using cannabis after having been drinking, which has implications for its relations to etiological correlates (e.g., motives, contexts) and outcomes (Pearson & Henson, 2013).…”
Section: The Present Studymentioning
confidence: 99%
“…In contrast, Waddell et al (2021) found greater support for substitution, such that for individuals with mean or low levels of impulsive traits (i.e., positive urgency and lack of perseverance), quantity of alcohol use was lower on days with co-use. Critically, there were several noteworthy differences between the samples—whereas Ito et al (2021) examined associations among a sample of college students, Waddell et al (2021) studied a slightly older sample of veterans, a group at increased risk for impulsivity and substance use (Bhalla et al, 2019; Gunn et al, 2020; Hawn et al, 2019; Meadows et al, 2018). These findings highlight the importance of examining person-level factors when considering one’s risk for increasing alcohol or cannabis use on co-use occasions.…”
Section: Patterns Predictors and Short- And Long-term Outcomes Of Co-usementioning
confidence: 99%
“…Daily diary and EMA designs are well suited to examine complementarity or substitution effects for alcohol and cannabis use (see Gunn et al, 2019; O’Hara et al, 2016). In this special issue, disparate findings emerged on this research question: Ito et al (2021) found evidence for complementarity in a sample of college students such that more alcohol was consumed on days when cannabis was used. In contrast, Waddell et al (2021) found greater support for substitution, such that for individuals with mean or low levels of impulsive traits (i.e., positive urgency and lack of perseverance), quantity of alcohol use was lower on days with co-use.…”
Section: Patterns Predictors and Short- And Long-term Outcomes Of Co-usementioning
confidence: 99%